ChemInform Abstract: Aza‐Conjugate Addition Methodology for the Synthesis of N‐Hydroxy‐isoindolin‐1‐ones. Issue 29 (June 2016) - Royo, Santiago; Chapman, Robert S. L.; Sim, Alisia M.; Peacock, Lucy R.; Bull, Steven D.
Abstract: Aryl aldehydes containing an ortho‐propiolate or propiolamide moiety are efficiently cyclized to N‐hydroxyisoindoline‐1‐ones, which are subsequently converted into the parent isoindoline‐1‐ones.